The Marriage Contract and Agreement - Kurniawan, Dede; Sayehu, Sayehu; Tarihoran, Naf’an (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The purpose of this study is to analyze betrothal (peminangan) and prenuptial agreements (perjanjian perkawinan) with reference to the Qur’an, Surah Al-Baqarah verse 235. This research employs a qualitative method with a descriptive approach. The data sources consist of books, dissertations, and articles, while data collection was carried out through online searches. The data were analyzed using a literature review technique. The findings indicate that betrothal represents an effort toward forming a marital bond between a man and a woman. In essence, betrothal, or proposal (melamar), etymologically means asking a woman to become a wife, either for oneself or on behalf of another. Betrothal is strongly encouraged in order for the prospective bride and groom to know each other, thus providing more benefits than disadvantages. The study also shows that all aspects of human life, including betrothal, are clearly regulated in the Qur’an and Hadith, as explicitly mentioned in Surah Al-Baqarah verse 235. Furthermore, a prenuptial agreement is a form of contract and, therefore, must fulfill the general requirements of validity as stipulated in Article 1320 of the Indonesian Civil Code, except where otherwise specifically regulated. Contribution: This study contributes to Islamic family law scholarship by offering a comprehensive interpretation of betrothal and prenuptial agreements from both Islamic sources (Qur’an and Hadith) and Indonesian civil law. It highlights the harmony and interaction between religious principles and national legal provisions, thereby providing a deeper understanding for academics, practitioners, and policymakers in strengthening legal certainty and religious compliance in marital practices